Global Education and National Pedagogy (Ethnopedagogical Experiences of Developed Asian Countries (With the Example of Academic Freedom)) - Khudayberganov Shuhrat Shavkat o‘g‘li (Genius Journals, 2023)
In this article, based on the experiences of global education and national pedagogy, opinions about the content of the wide introduction of academic freedom in the development of higher education institutions are expressed.
Keywords: academic freedom; financial independence